A50: Mental Health and Healthcare Utilization in Children with SLE and MCTD. Issue 11 (March 2014) - Knight, Andrea; Weiss, Pamela; Morales, Knashawn; Keren, Ron
Abstract : Background/Purpose: Depression and anxiety are prevalent in children with systemic lupus erythematosus (SLE), representing a health‐related burden. SLE healthcare utilization is high, and the impact of these disorders on utilization is unclear. We aimed to characterize the association of depression and anxiety with healthcare utilization in children with SLE and the SLE‐like syndrome of mixed connective tissue disease (MCTD). Methods: We conducted a cross‐sectional analysis of pediatric‐onset SLE and MCTD patients with disease duration >=6 months, consecutively recruited from CHOP rheumatology and nephrology outpatient clinics. The Patient Health Questionnaire 9 (PHQ‐9) and the Screen for Child Anxiety Related Disorders (SCARED) were used to measure depression and anxiety, respectively. The primary outcome was average outpatient visits per person‐year, measured as a composite of rheumatology, nephrology, primary care and emergency department (ED) visits within the preceding year. Secondary outcomes were average hospital visits and telephone consultations to rheumatology/nephrology per person‐year, within the preceding year. Multivariable negative binomial regression analysis was performed including the following covariates: age, race/ethnicity, education level, disease duration and disease activity. Results: We recruited 42 patients, with a median SLEDAI (SLE Disease Activity Index) score of 2 (IQR 0, 4) and median physician VAS (visual assessment score) of 0 (IQR 0, 1). We identified symptoms of depression in 8 patients (19%), anxiety in 9 patients (21%), and comorbid depression and anxiety in 4 patients (10%). Only 14% of patients with positive screens for depression and/or anxiety had previous mental health care. The average number of outpatient visits per person‐year was 4.6 [95% confidence interval (CI) 3.4–6.2], hospitalizations 0.2 (95% CI 0.09–0.66) and phone consultations 0.8 (95% CI 0.53–1.35). In multivariable analysis, there was a statistically significant decrease in outpatient visits for those with depressive symptoms compared to those without (IRR = 0.6, 95%CI 0.4–0.9, p = 0.02). Secondary analysis showed a statistically significant decrease in primary care provider (PCP) visits in the depressed group (IRR = 0.33, 95%CI 0.16–0.7, p < 0.01); however, there was no difference in rheumatology, nephrology or ED visits. Depressive symptoms were also not associated with differences in hospitalizations or phone consultations. There was no significant association of anxiety symptoms with the healthcare utilization outcomes. Conclusion: Depression and anxiety symptoms were prevalent in this cohort of children with minimally active SLE and MCTD. Those with depressive symptoms had significantly decreased outpatient visits, particularly to the PCP. Rheumatology and nephrology providers are therefore an important point of contact for identifying mental health disorders in these patients. Further investigation is needed to understand the patient and caregiver factors contributing to differences in healthcare provider contact for pediatric SLE patients with depressive symptoms.